(untitled) (Universal International Scientific Journal, 2026)
This scientific article analyzes the psychological possibilities of the process of modeling the professional career of young people. In modern society, the issue of choosing a profession and professional development is an important stage in the life of young people. Therefore, an in-depth study of psychological factors in this process is of urgent importance. A person’s interests, motivation, abilities, values, and level of self-awareness are considered important factors in determining a professional direction. The role of psychological counseling, diagnostics, and developmental training in the process of career modeling is also highlighted.